Adverse drug reactions in the department of dermatology at a tertiary care hospital: a prospective study - Sowmyanarayan, Sujatha; K. A., Rajeshwari; Banerjee, Swati (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To study cutaneous adverse drug reactions with regard to their clinical pattern. etiology, causality and severity. Methods: It was a prospective study undertaken in a 300 bedded tertiary care hospital. Patients with cutaneous ADRs presenting in Dermatology OPD were studied. Causality and severity of the adverse drug reactions were analysed and other parameters such as gender wise distribution of the ADRs and types of ADR were studied. Results: 35 cases of ADRs were enrolled for the study in the duration of Sept.2016 to May 2017. The majority of the patients were in the age group of 21-30 years (37.14%). The most common CADRs were Acne vulgaris (22.86%), followed by Fixed Drug eruption (11.43%) and Tinea cruris (8.57%). The most common class of drugs causing ADRs were topical steroids (64%), followed by non-steroidal anti-inflammatory drugs (14.29%). Conclusions: Female preponderance was seen. Topical steroids were the most offending drug followed by Diclofenac Sodium, the analgesic. Causality assessment showed a high score of Certain category. These variations may be explained by variations in drug usage patterns. The knowledge of the adverse drug reactions and the drugs causing them is essential for the clinician so that the choice of drug therapy can be made keeping these adverse drug reactions in mind.